Counterclockwise post-emplacement evolution of metatroctolites from the Aluminé Igneous-Metamorphic Complex, Neuquén, Argentina - Urraza, Ivana Alejandra (2015)
Post-crystallization evolution of the metatroctolites of the Ñorquinco lake zone, Aluminé Igneous-Metamorphic Complex, is analyzed. These mafic rocks show coronas around olivine, composed of Opx, Cpx, Spl and Amp (Hbl1and Hbl2). The temporal evolution of these rocks was evaluated via petrographic analysis and the construction of a suitable pseudosection based on the whole-rock chemical composition. This analysis was complemented with classic geothermobarometry, from which four stages on the P-T path were established: A. Starting point lies in the stability field of the Pl-Ol-Opx-Cpx-H2O, with P-T of 936 ºC and 2.7 kbar, respectively, indicative of granulite facies conditions;B. Another point in the trajectory is represented by first appearance of amphibole. P-T conditions for Hbl1-Pl are 780 °C and 5.9 Kbar, respectively.; C. The third point is characterized by the presence of Hbl2 and Spl and the disappearance of Ol, leading to the association Pl-Opx-Cpx-Hbl2-Spl-H2O. Equilibrium temperature and pressure for this stage are 780 ºC and 5.69 Kbar, respectively; and D. The last point in the path implies the disappearance of Cpx and the retrogression of the phases to Chl with, a concomitant consumption of excess water. Both the equilibrium temperature (694.2 ºC) for the stable association Pl-Opx-Hbl2-Spl-Chl, and the narrow stability pressure range (4.5-5.2 Kbar), are constrained by the absence of olivine and garnet. The defined portion of the P-T path indicates cooling from granulite to amphibolite facies with a concomitant pressure increment, defining a counter-clockwise P-T path. U-Pb zircon ages determined for basement xenoliths in metatroctolites and gabbroic inclusions in granodiorites, allows constraining the emplacement of Ñorquinco lake metatroctolites to Upper Paleozoic times.